Severity of Childhood Obstructive Sleep Apnea and Hypertension Improved after Adenotonsillectomy. (March 2015) - Lee, Li-Ang; Li, Hsueh-Yu; Lin, Yu-Sheng; Fang, Tuan-Jen; Huang, Yu-Shu; Hsu, Jen-Fu; Wu, Che-Ming; Huang, Chung-Guei
Objective: To report improvements in childhood obstructive sleep apnea (OSA) and hypertension after adenotonsillectomy. Study Design: Case series with planned data collection. Setting: Tertiary referral center. Subjects and Methods: Fifty consecutive patients (36 boys and 14 girls; median age, 7.0 years) who underwent plasma knife–assisted total tonsillectomy and adenoidectomy for OSA between January 2010 and March 2013 were assessed with the body mass index z score, apnea-hypopnea index (AHI), systolic blood pressure (BP), and diastolic BP at baseline and at ≥6 months postoperatively. Changes in these parameters were statistically analyzed using nonparametric tests with the bootstrap approach. Results: The median follow-up period was 9.6 months. Postoperatively, the median AHI significantly reduced from 9.8 to 1.6 ( P < .001). Although the median systolic BP and diastolic BP insignificantly changed in the overall group, both were significantly reduced in children with preoperative hypertension (systolic: from 119.0 to 113.0 [ P = .038]; diastolic: from 79.0 to 68.0 [ P = .005]). Accordingly, the hypertension rate significantly reduced from 34% to 14% ( P = .006). However, the change in OSA severity was not well correlated with the change in hypertension severity. In multiple logistic regression analysis with forward selection, a combination of preoperative hypertension and severe OSA was a significant predictor of postoperative hypertension (relative risk, 15.4; 95% confidence interval, 3.7-64.3; P < .001). Conclusion: The decreased hypertension rate indicates that a reduction of the AHI is not all that matters after adenotonsillectomy in childhood OSA. However, patients with preoperative severe OSA and hypertension need careful management of their elevated BP despite surgical treatment.